2009
DOI: 10.1016/s0140-6736(09)60371-8
|View full text |Cite
|
Sign up to set email alerts
|

Intracerebral haemorrhage

Abstract: Intracerebral haemorrhage is an important public health problem leading to high rates of death and disability in adults. Although the number of hospital admissions for intracerebral haemorrhage has increased worldwide in the past 10 years, mortality has not fallen. Results of clinical trials and observational studies suggest that coordinated primary and specialty care is associated with lower mortality than is typical community practice. Development of treatment goals for critical care, and new sequences of ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
1,014
1
30

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,363 publications
(1,053 citation statements)
references
References 147 publications
(202 reference statements)
8
1,014
1
30
Order By: Relevance
“…There are numerous causes, risk factors, and precipitating/contributing factors and each case is usually multifactorial in origin. The major underlying causes include the pathophysiological changes in deep perforating arteries associated with chronic hypertension (which may include lipohyalinosis and microaneurysms), amyloid angiopathy, and vascular malformations such as aneurysms, arteriovenous malformations, and cavernomas (Qureshi et al, 2009). Important precipitating/contributing factors may include acute hypertension, abnormal coagulation, and thrombolysis.…”
Section: A Heterogeneous Condition With Multiple Etiologiesmentioning
confidence: 99%
“…There are numerous causes, risk factors, and precipitating/contributing factors and each case is usually multifactorial in origin. The major underlying causes include the pathophysiological changes in deep perforating arteries associated with chronic hypertension (which may include lipohyalinosis and microaneurysms), amyloid angiopathy, and vascular malformations such as aneurysms, arteriovenous malformations, and cavernomas (Qureshi et al, 2009). Important precipitating/contributing factors may include acute hypertension, abnormal coagulation, and thrombolysis.…”
Section: A Heterogeneous Condition With Multiple Etiologiesmentioning
confidence: 99%
“…Andres et al 5 has reported that notwithstanding the differences in the procedures, including the route, NSCs migrate into the perihematomal region and survive after transplantation in ICH animals, but clinically, surgical evacuation is done either with open craniotomy or stereotactic and endoscopic techniques to prevent expansion, to decrease mass effects, and to block the release of neuropathic products from hematomas at the acute stage of ICH. 3 Therefore, intraparenchymal transplantation was used in this present study, because it is possible to graft cells during surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneous intracerebral hemorrhage (ICH) accounts for 10 to 15% of all strokes worldwide or 10 to 30 cases per 100,000 people per year [1]. Patients with ICH show the worst outcome of all stroke subtypes with a 30-day mortality rate of 30 to 50% [2][3][4][5].…”
Section: Incidencementioning
confidence: 99%
“…In addition, after the first year, more than 75% of all patients are severely disabled or deceased [1,4]. Many patients, families, and providers wish to know, in the acute phase, what the patient's outcome will be ultimately.…”
Section: Outcomementioning
confidence: 99%